Preparation process of basalt fiber toughened solid waste-based supersulfate cement material

Through the surface modification of Xuanwu Fiber, including low -temperature lime water treatment and paraffin oil ultrasound treatment, the performance decline of fiber in a strong alkali environment has been solved, which significantly improves its alkali resistance and the toughness of ultra -sulfate cement.

CN119143461BActive Publication Date: 2025-01-24SHANDONG ZHENGHENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411616109.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-24
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Basalt fibers are easily damaged in a strong alkaline environment of supersulfate cement, resulting in limited toughness enhancement effect.

Method used

By placing Xuanwu Fiber in saturated lime water for low temperature and static treatment, the active surface is formed, and then ultrasound treatment with paraffin oil and lithium carbonate or lithium sulfate meal to enhance the alkali resistance of the fiber.

Benefits of technology

It effectively improves the alkali erosion resistance of basalt fiber, enhances the toughness and crack resistance of super sulfate cement, and ensures the improvement of its mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143461B_ABST
    Figure CN119143461B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of supersulfate cement preparation, and specifically discloses a preparation process of basalt fiber-reinforced solid waste-based supersulfate cement material. The process comprises the following steps: (1) placing basalt fiber in saturated lime water and letting it stand. Then separating the fiber, washing it, dispersing it in clean water for hydrothermal reaction, and obtaining surface-modified basalt fiber. (2) placing the surface-modified basalt fiber in hot paraffin oil for ultrasonic treatment, and after completion, taking out the fiber and mixing it with lithium carbonate or lithium sulfate powder to obtain alkali-resistant modified basalt fiber. (3) taking granulated blast furnace slag, steel slag fine aggregate, sulfate activator, alkali activator, alkali-resistant modified basalt fiber, and water reducer as raw materials. Mixing the above raw materials and stirring them evenly, and then adding water and stirring them evenly to obtain the material. The above process of the present invention can effectively improve the alkali erosion resistance of basalt fiber and improve the strengthening effect on the toughness of supersulfate cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supersulfate cement preparation, and in particular to a preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Super sulphated cement (SSC) is a green, environmentally friendly, low-carbon hydraulic cementitious material that is formed by grinding industrial solid waste granulated blast furnace slag as the main cementitious material, adding sulfate activators and alkali activators and other additives. The alkali activator reacts with the active SiO2 and Al2O3 in the granulated blast furnace slag to generate hydrated calcium silicate and hydrated calcium aluminate, and the sulfate activator further reacts with the hydrated calcium aluminate to form hydrated calcium sulfoaluminate. Therefore, the main hydration products of gypsum slag cement are calcium aluminate and hydrated calcium silicate, followed by calcium aluminate hydrate (C2AH8), calcium aluminosilicate hydrate (C2ASH8) and other components. This cement has the advantages of good sulfate resistance, low hydration heat, good impermeability, high strength, etc., and can be used in engineering fields such as construction, roads, and bridges.

[0004] Although super-sulfate cement has high strength, it has the problem of insufficient toughness. Basalt fiber is a fiber material with SiO2 as the main component, which is made of basalt ore as raw material and is quickly drawn after high-temperature melting. Its mineral components are mainly quartz, orthoclase, plagioclase, pyroxene, corundum, nepheline, etc. Basalt fiber has the advantages of high elastic modulus and high tensile strength. Therefore, adding basalt fiber to super-sulfate cement helps to improve its toughness, crack resistance and other mechanical properties. However, basalt fiber is easily damaged and its performance deteriorates in the strong alkaline environment of super-sulfate cement, which limits the effect of basalt fiber on improving the toughness of super-sulfate cement and fails to play its due effect. Summary of the invention

[0005] In view of the above problems, the present invention provides a preparation process of basalt fiber-reinforced solid waste-based supersulfate cement material, which can effectively improve the alkali corrosion resistance of basalt fiber and enhance the toughness of supersulfate cement. Specifically, the technical solution of the present invention is as follows.

[0006] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0007] (1) Place basalt fiber in saturated lime water and then let it stand at 2-5°C. After completion, separate the fiber, wash it, disperse it in clean water for hydrothermal reaction, separate the fiber and dry it to obtain surface-modified basalt fiber.

[0008] (2) placing the surface-modified basalt fiber in hot paraffin oil for ultrasonic treatment, taking out the fiber and mixing it with lithium carbonate or lithium sulfate powder to obtain alkali-resistant modified basalt fiber.

[0009] (3) Take 110-125 parts by weight of granulated blast furnace slag, 40-60 parts by weight of steel slag fine aggregate, 16-24 parts by weight of sulfate activator, 2-5 parts by weight of alkali activator, 10-14 parts by weight of the alkali-resistant modified basalt fiber, and 1.8-2.6 parts by weight of water reducer as raw materials. The steel slag fine aggregate has been treated to eliminate free calcium oxide. Mix the above raw materials and add water at a water-cement ratio of 0.35-0.45 and stir evenly to obtain the basalt fiber toughened steel slag supersulfate cement.

[0010] Furthermore, in step (1), the material-liquid ratio of the basalt fiber to saturated lime water is 1 g: 10-40 ml. Optionally, the length of the basalt fiber is 5-30 mm.

[0011] Furthermore, in step (1), the standing time is 12 to 24 hours to perform surface treatment on the basalt fiber.

[0012] Furthermore, in step (1), the ratio of the fiber to clean water is 1g:20-40ml.

[0013] Furthermore, in step (1), the temperature of the hydrothermal reaction is 160-200° C., and the time is 1-3 hours.

[0014] Furthermore, in step (1), the drying temperature is 80-100° C., and the fiber is dried at this temperature until the weight is constant, so as to fully remove the moisture in the fiber.

[0015] Furthermore, in step (2), the temperature of the paraffin oil is 60-80° C., and the ultrasonic time is 10-20 min, so that the paraffin oil fully infiltrates the fiber surface.

[0016] Furthermore, in step (2), the mass ratio of the fiber to lithium carbonate or lithium sulfate powder is 1:0.3-0.42.

[0017] Furthermore, in step (3), the sulfate activator includes chemically pure gypsum and / or solid waste gypsum. The solid waste gypsum includes at least one of desulfurized gypsum, fluorinated gypsum, phosphogypsum, etc.

[0018] Furthermore, in step (3), the alkali activator includes at least one of Portland cement clinker, calcium hydroxide, etc.

[0019] Furthermore, in step (3), the water reducer includes any one of a polycarboxylate water reducer, a naphthalene-based water reducer, a melamine-based water reducer, a lignin sulfonate water reducer, and the like.

[0020] Furthermore, in step (3), the method for eliminating free calcium oxide from steel slag fine aggregate comprises the following steps: mixing steel slag powder with tetraethyl orthosilicate and stirring evenly, and then calcining to form aluminum-doped γ-C2S by reacting the free calcium oxide and aluminum element in the steel slag with the active calcium dioxide particles formed by decomposition of tetraethyl orthosilicate. After completion, the product is naturally cooled to room temperature, crushed and sieved to obtain steel slag fine aggregate.

[0021] Furthermore, the ratio of the steel slag powder to tetraethyl orthosilicate is a calcium silicon (Ca / Si) molar ratio of 2-2.1:1.

[0022] Furthermore, the calcination temperature is 1400-1450° C. and the calcination time is 3-4 hours.

[0023] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0024] (1) In view of the problem that basalt fiber has insufficient alkali resistance and is easily damaged in the strong alkaline environment of supersulfate cement, resulting in performance degradation, the present invention first treats basalt fiber in low-temperature saturated lime water. During this process, the fiber surface is first depolymerized under the action of hydroxide ions to form an active surface, and then forms a -Ca-Si- layer with calcium ions in saturated lime water. As the -Ca-Si- layer is continuously generated and coated on the fiber surface, the reaction process gradually slows down until it stops. Since these reactions occur unevenly, they occur preferentially at defects on the fiber surface, so that the fiber surface becomes rough after the reaction is completed. In addition, since the above reaction is carried out at a low temperature, the fiber surface can be well prevented from being excessively eroded. After further hydrothermal reaction, the -Ca-Si- layer becomes denser and more closely combined with the fiber matrix, which repairs the fiber matrix, thereby improving the roughness of the fiber surface while ensuring that it maintains good mechanical properties, preventing the improvement effect of the mechanical properties of supersulfate cement from decreasing. The present invention soaks the basalt fiber treated as above in paraffin oil, which can effectively improve the fiber's alkali resistance after infiltration, and maintain good stability in an alkaline environment. At the same time, the fiber also has good dispersibility, avoiding uneven dispersion in cement and affecting its mechanical properties. In addition, the present invention also uses the paraffin oil on the fiber surface to load lithium carbonate or lithium sulfate powder, so that the lithium carbonate or lithium sulfate is dispersed into cement using the fiber with good dispersibility to accelerate its hydration rate and improve its early strength.

[0025] (2) The present invention utilizes the free calcium oxide in steel slag, utilizes the active silica formed by decomposition of ethyl orthosilicate to react with free calcium oxide to form C2S, and utilizes the aluminum element in steel slag to dope the C2S to further improve its stability, so that it is converted into γ-C2S during the natural cooling process, and obtains steel slag fine aggregate containing γ-C2S. Since the hydration activity of γ-C2S is very low, but the reaction activity with carbon dioxide is very high. Therefore, after this fine aggregate enters the supersulfate cement, the hydration products such as ettringite formed in the subsequent hydration reaction are rich in γ-C2S, which can react and fix the carbon dioxide entering the supersulfate cement of the present invention, thereby reducing the decomposition and destruction of ettringite by carbon dioxide. The present invention not only realizes the utilization of steel slag solid waste, but also eliminates the problem of poor volume stability caused by free calcium oxide in steel slag, and converts this unfavorable factor into a favorable factor for improving the carbonation resistance of supersulfate cement, thereby improving the durability of supersulfate cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which constitute a part of the present invention, are used to provide further understanding of the present invention and shall not constitute improper limitation of the present invention.

[0027] Figure 1The XRD pattern of the steel slag fine aggregate prepared in Example 1 below.

[0028] Figure 2 This is a compressive strength test chart of the supersulfate cement prepared in Example 1 below.

[0029] Figure 3 This is a graph showing the flexural strength test of the supersulfate cement prepared in Example 1 below. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. Now the technical solution of the present invention is further described in conjunction with specific embodiments.

[0031] Example 1

[0032] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0033] (1) Mix basalt fiber with a length of 10 mm and saturated lime water in a ratio of 1 g: 25 ml and stir evenly. Then place it in an environment of 4°C and let it stand for 18 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 30 ml in a high-pressure reactor for hydrothermal reaction (temperature 160°C, time 3 hours). After completion, filter out the fiber and dry it at 100°C to constant weight to obtain surface-modified basalt fiber.

[0034] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 70° C. and ultrasonically treated for 20 min at an ultrasonic power of 300 W. The fiber is then taken out and mixed with lithium carbonate powder in a mass ratio of 1:0.35 and stirred evenly to obtain alkali-resistant modified basalt fiber for later use.

[0035] (3) Steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.05:1, and then heated to 1420°C at a heating rate of 15°C / min for 4 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm. Its XRD was as follows: Figure 1 shown.

[0036] (4) Take 110 parts by weight of granulated blast furnace slag, 40 parts by weight of steel slag fine aggregate of this embodiment, 20 parts by weight of dihydrate gypsum, 2 parts by weight of calcium hydroxide, 10 parts by weight of the alkali-resistant modified basalt fiber, and 1.8 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.38 and stir for 2 minutes to obtain a supersulfated cement material.

[0037] According to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 28d compressive strength of the supersulfate cement material in this embodiment (respectively Figure 2 As shown), flexural strength test (as shown Figure 3 The carbonation resistance of the super sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: compressive strength = 53.64MPa, flexural strength = 13.23MPa, axial tensile strength = 5.71MPa, and carbonation depth = 3.7mm.

[0038] Example 2

[0039] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0040] (1) Mix 5 mm long basalt fiber and saturated lime water in a ratio of 1 g: 10 ml and stir evenly. Then place it in an environment of 2°C and let it stand for 24 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 20 ml in a high-pressure reactor for hydrothermal reaction (temperature 180°C, time 2.5 hours). After completion, filter out the fiber and dry it at 90°C to constant weight to obtain surface-modified basalt fiber.

[0041] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 60° C. and ultrasonically treated for 20 min at an ultrasonic power of 300 W. The fiber is then taken out and mixed with lithium carbonate powder at a mass ratio of 1:0.3 and stirred evenly to obtain alkali-resistant modified basalt fiber for later use.

[0042] (3) The steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.1:1, and then heated to 1400°C at a heating rate of 15°C / min and kept at that temperature for 4 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm.

[0043] (4) Take 115 parts by weight of granulated blast furnace slag, 50 parts by weight of steel slag fine aggregate of this embodiment, 16 parts by weight of desulfurized gypsum, 3 parts by weight of calcium hydroxide, 12 parts by weight of the alkali-resistant modified basalt fiber, and 2.2 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.45 and stir for 2 minutes to obtain a supersulfated cement material.

[0044] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 50.19MPa, 28d flexural strength = 11.86MPa, axial tensile strength = 5.24MPa, carbonation depth = 2.5mm.

[0045] Example 3

[0046] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0047] (1) Mix basalt fiber with a length of 30 mm and saturated lime water in a ratio of 1 g: 40 ml and stir evenly. Then place it in an environment of 5°C and let it stand for 12 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 40 ml in a high-pressure reactor for hydrothermal reaction (temperature 200°C, time 1 hour). After completion, filter out the fiber and dry it at 80°C to constant weight to obtain surface-modified basalt fiber.

[0048] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 80° C. and ultrasonically treated for 10 min at an ultrasonic power of 350 W. The fiber is then taken out and mixed with lithium sulfate powder at a mass ratio of 1:0.42 and stirred evenly to obtain alkali-resistant modified basalt fiber for later use.

[0049] (3) Steel slag powder and ethyl orthosilicate were mixed evenly in a calcium-silicon molar ratio of 2:1, and then heated to 1450°C at a heating rate of 15°C / min and kept at this temperature for 3 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm.

[0050] (4) Take 125 parts by weight of granulated blast furnace slag, 60 parts by weight of steel slag fine aggregate of this embodiment, 24 parts by weight of fluorgypsum, 5 parts by weight of 42.5 silicate cement clinker, 14 parts by weight of the alkali-resistant modified basalt fiber, and 2.6 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.35 and stir for 2 minutes to obtain a supersulfated cement material.

[0051] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 54.81MPa, 28d flexural strength = 14.92MPa, axial tensile strength = 6.03MPa, carbonation depth = 4.6mm.

[0052] Example 4

[0053] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0054] (1) Mix basalt fiber with a length of 30 mm and saturated lime water in a ratio of 1 g: 40 ml and stir evenly. Then place it in an environment of 5°C and let it stand for 12 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 40 ml in a high-pressure reactor for hydrothermal reaction (temperature 200°C, time 1 hour). After completion, filter out the fiber and dry it at 80°C to constant weight to obtain surface-modified basalt fiber.

[0055] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 80° C. and ultrasonically treated for 10 min at an ultrasonic power of 350 W. The fiber is then taken out and mixed with lithium sulfate powder at a mass ratio of 1:0.42 and stirred evenly to obtain alkali-resistant modified basalt fiber for later use.

[0056] (3) Take 125 parts by weight of granulated blast furnace slag, 60 parts by weight of steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm, 24 parts by weight of fluorgypsum, 5 parts by weight of 42.5 silicate cement clinker, 14 parts by weight of the alkali-resistant modified basalt fiber of this embodiment, and 2.6 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.35 and stir for 2 minutes to obtain a supersulfated cement material.

[0057] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 45.52MPa, 28d flexural strength = 9.88MPa, axial tensile strength = 4.16MPa, carbonation depth = 12.1mm.

[0058] Example 5

[0059] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0060] (1) Steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.05:1, and then heated to 1420°C at a heating rate of 15°C / min for 4 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm.

[0061] (2) Take 110 parts by weight of granulated blast furnace slag, 40 parts by weight of steel slag fine aggregate of this embodiment, 20 parts by weight of dihydrate gypsum, 2 parts by weight of calcium hydroxide, 10 parts by weight of basalt fiber with a length of 10 mm, and 1.8 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.38 and stir for 2 minutes to obtain a supersulfated cement material.

[0062] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 38.12MPa, 28d flexural strength = 7.36MPa, axial tensile strength = 3.22MPa, carbonation depth = 4.2mm.

[0063] Example 6

[0064] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0065] (1) Mix 5 mm long basalt fiber and saturated lime water in a ratio of 1 g: 10 ml and stir evenly. Then place it in an environment of 2°C and let it stand for 24 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 20 ml in a high-pressure reactor for hydrothermal reaction (temperature 180°C, time 2.5 hours). After completion, filter out the fiber and dry it at 90°C to constant weight to obtain surface-modified basalt fiber.

[0066] (2) Steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.1:1, and then heated to 1400°C at a heating rate of 15°C / min and kept at that temperature for 4 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm.

[0067] (3) Take 115 parts by weight of granulated blast furnace slag, 50 parts by weight of steel slag fine aggregate of this embodiment, 16 parts by weight of desulfurized gypsum, 3 parts by weight of calcium hydroxide, 12 parts by weight of the surface-modified basalt fiber of this embodiment, and 2.2 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.45 and stir for 2 minutes to obtain a supersulfated cement material.

[0068] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 41.33MPa, 28d flexural strength = 8.54MPa, axial tensile strength = 3.87MPa, carbonation depth = 3.1mm.

[0069] Example 7

[0070] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0071] (1) A basalt fiber with a length of 10 mm was placed in hot paraffin oil at 70° C. and ultrasonically treated for 20 min at an ultrasonic power of 300 W. The fiber was then taken out and mixed with lithium carbonate powder at a mass ratio of 1:0.35 and stirred evenly to obtain an alkali-resistant modified basalt fiber for later use.

[0072] (2) Steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.05:1, and then heated to 1420°C at a heating rate of 15°C / min for 4 hours. Then the mixture was naturally cooled to room temperature, and the calcined product was crushed and sieved to obtain steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm.

[0073] (3) Take 110 parts by weight of granulated blast furnace slag, 40 parts by weight of steel slag fine aggregate of this embodiment, 20 parts by weight of dihydrate gypsum, 2 parts by weight of calcium hydroxide, 10 parts by weight of the alkali-resistant modified basalt fiber, and 1.8 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.38 and stir for 2 minutes to obtain a supersulfated cement material.

[0074] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 47.76MPa, 28d flexural strength = 10.08MPa, axial tensile strength = 4.51MPa, carbonation depth = 3.9mm.

[0075] Example 8

[0076] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0077] (1) Mix basalt fiber with a length of 30 mm and saturated lime water in a ratio of 1 g: 40 ml and stir evenly. Then place it in an environment of 5°C and let it stand for 12 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 40 ml in a high-pressure reactor for hydrothermal reaction (temperature 200°C, time 1 hour). After completion, filter out the fiber and dry it at 80°C to constant weight to obtain surface-modified basalt fiber.

[0078] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 80° C. and ultrasonically treated for 10 min at an ultrasonic power of 350 W. After being taken out, the alkali-resistant modified basalt fiber is obtained and set aside.

[0079] (3) Take 125 parts by weight of granulated blast furnace slag, 60 parts by weight of steel slag fine aggregate prepared in Example 3, 24 parts by weight of fluorgypsum, 5 parts by weight of 42.5 silicate cement clinker, 9.86 parts by weight of the alkali-resistant modified basalt fiber of this example, 4.14 parts by weight of lithium sulfate powder, and 2.6 parts by weight of polycarboxylate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.35 and stir for 2 minutes to obtain a supersulfated cement material.

[0080] According to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 3d compressive strength of the supersulfate cement material of this embodiment was tested. The results showed that the 3d compressive strength of this embodiment decreased by 4.81% compared with that of Example 3, indicating that the early strength of the sulfate cement material prepared in this embodiment decreased to a certain extent compared with that of Example 3.

[0081] Example 9

[0082] A preparation process of a basalt fiber-reinforced solid waste-based supersulfate cement material comprises the following steps:

[0083] (1) Mix 5 mm long basalt fiber and saturated lime water in a ratio of 1 g: 10 ml and stir evenly. Then place it in an environment of 2°C and let it stand for 24 hours. After completion, filter out the fiber and wash it with water. Then place the fiber and clean water in a ratio of 1 g: 20 ml in a high-pressure reactor for hydrothermal reaction (temperature 180°C, time 2.5 hours). After completion, filter out the fiber and dry it at 90°C to constant weight to obtain surface-modified basalt fiber.

[0084] (2) The surface-modified basalt fiber is placed in hot paraffin oil at 60° C. and ultrasonically treated for 20 min at an ultrasonic power of 300 W. The fiber is then taken out and mixed with lithium carbonate powder at a mass ratio of 1:0.3 and stirred evenly to obtain alkali-resistant modified basalt fiber for later use.

[0085] (3) The steel slag powder and ethyl orthosilicate were mixed evenly at a calcium-silicon molar ratio of 2.1:1 and allowed to stand at room temperature for 4 hours. After sieving, steel slag fine aggregate with a particle size distribution between 0.2 and 0.5 mm was obtained.

[0086] (4) Take 115 parts by weight of granulated blast furnace slag, 50 parts by weight of steel slag fine aggregate prepared in this example, 16 parts by weight of desulfurized gypsum, 3 parts by weight of calcium hydroxide, 12 parts by weight of alkali-resistant modified basalt fiber prepared in this example, and 2.2 parts by weight of sodium lignin sulfonate water reducer. Mix the above raw materials and stir for 5 minutes, then add clean water at a water-cement ratio of 0.45 and stir for 2 minutes to obtain supersulfated cement material.

[0087] The 28d compressive strength, flexural strength and axial tensile strength of the super-sulfate cement material of this embodiment were tested according to GBT 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The anti-carbonation performance of the super-sulfate cement material of this embodiment was tested according to GBT 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The results are: 3d compressive strength = 49.05MPa, 28d flexural strength = 11.13MPa, axial tensile strength = 5.06MPa, carbonation depth = 10.4mm.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.

Claims

1. A preparation process of basalt fiber toughened solid waste-based supersulfate cement material, characterized in that: The steps include: (1) placing basalt fiber in saturated lime water and then standing at 2-5°C; after completion, separating the fiber, washing it and dispersing it in clean water for hydrothermal reaction; after completion, separating the fiber and drying it to obtain surface-modified basalt fiber; (2) placing the surface-modified basalt fiber in hot paraffin oil for ultrasonic treatment, then taking out the fiber and mixing it with lithium carbonate or lithium sulfate powder to obtain alkali-resistant modified basalt fiber; (3) Take 110-125 parts by weight of granulated blast furnace slag, 40-60 parts by weight of steel slag fine aggregate, 16-24 parts by weight of sulfate activator, 2-5 parts by weight of alkali activator, 10-14 parts by weight of the alkali-resistant modified basalt fiber, and 1.8-2.6 parts by weight of water reducer as raw materials; the steel slag fine aggregate has been treated to eliminate free calcium oxide; mix the above raw materials, add water at a water-cement ratio of 0.35-0.45, and stir evenly.

2. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the material-liquid ratio of the basalt fiber to saturated lime water is 1 g: 10-40 mL.

3. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the length of the basalt fiber is 5 to 30 mm.

4. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the standing time is 12 to 24 hours.

5. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the ratio of the fiber to clean water is 1 g: 20-40 mL.

6. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 160-200° C., and the time is 1-3 hours.

7. The preparation process of basalt fiber toughened solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (1), the drying temperature is 80-100° C., and the product is dried at this temperature until the weight is constant.

8. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (2), the mass ratio of the fiber to lithium carbonate or lithium sulfate powder is 1:0.3-0.

42.

9. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (2), the temperature of the paraffin oil is 60-80° C., and the ultrasonic time is 10-20 min.

10. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (3), the sulfate activator includes chemically pure gypsum and / or solid waste gypsum.

11. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (3), the alkali activator includes at least one of Portland cement clinker and calcium hydroxide.

12. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 1, characterized in that: In step (3), the water reducer includes any one of a polycarboxylate water reducer, a naphthalene-based water reducer, a melamine-based water reducer, and a lignin sulfonate water reducer.

13. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to any one of claims 1 to 12, characterized in that: In step (3), the method for eliminating free calcium oxide from steel slag fine aggregate comprises the following steps: mixing steel slag powder with tetraethyl orthosilicate and stirring evenly, and then calcining to form aluminum-doped γ-C2S by reacting the free calcium oxide and aluminum element in the steel slag with active silica particles formed by decomposition of tetraethyl orthosilicate; and naturally cooling to room temperature after completion, crushing and screening the product to obtain steel slag fine aggregate.

14. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 13, characterized in that: The ratio of the steel slag powder to ethyl orthosilicate is a calcium-silicon molar ratio of 2-2.1:

1.

15. The process for preparing basalt fiber-reinforced solid waste-based supersulfate cement material according to claim 13, characterized in that: The calcination temperature is 1400-1450° C. and the calcination time is 3-4 hours.

Citation Information

Patent Citations

  • High-toughness super sulfate cement and preparation method thereof

    CN111205002A

  • Basalt fiber reinforced concrete and preparation method thereof

    CN116332591A